Problemi neformalnih (obiteljskih) njegovatelja u skrbi za osobe s demencijom - kvalitativni pristup - Tilinger, Ana (Array, 2019)
Alzheimer’s disease, as the most common form of dementia, is a progressive, incurable condition that can lead to total dependence on others. The whole family, especially the family member who serves as caregiver of a patient, faces many problems and is in a very difficult situation. By taking over the demanding role of care for the family member, the carer often becomes a “victim of the disease” who needs to find ways to shoulder everything that the disease brings. Studies outside Croatia show that some interventions assist caregivers in their role, such as knowledge of the disease process, knowledge of nutrition and nursing of the affected person, knowledge of caregiver-related stress management, and instructions on how to address the problems associated with the patient’s changed behaviour. In order to gain insight into the problems encountered by informal carers in the care of a member of the family with dementia in Croatia, we examined their experiences. The method used for this qualitative research was a semi-structured interview. The results of this research suggest that informal caregivers are faced with demanding tasks of caring, difficulties in communication with the sick, system-level problems, social isolation and disrupted psychophysical functioning. The work emphasises the importance of educating informal caregivers about different aspects of care with the aim of facilitating a caring role, expertise in working with patients, and informing and sensitising the local community and society about the needs of informal caregivers.